Analysis of Hydraulic Flood Control Structure at Putat Boro River - Ruhban Ruzziyatno (Journal of the Civil Engineering Forum, 2013)
Putat Boro River is one of the main drainage systems of Surakarta city which drains into Bengawan Solo river. The primary problem when flood occur is the higher water level of Bengawan Solo than Boro River and then backwater occur and inundates Putat Boro River. The objective of the study is to obtain operational method of Putat Boro River floodgate to control both inflows and outflows not only during flood but also normal condition. It also aims to know the Putat Boro rivers floodgate operational function to reduce inundation. Putat Boro river water level variation and Bengawan Solo river water level variation were used for simulation of Boro river floodgate routing. The simulation used 10-year inflows, 50-year inflows, and 100-year inflows return period and Boro water level variation are +82.50 m, +83.00 m and +84.00 m. The results of the study show that the effective opening of floodgate are 0.35 m - 0.55 m for +82.05 m of Bengawan Solo water level, 0.50 m – 0.65 m for +82.55 m of Bengawan Solo water level and 0.70 m – 0.85 m for +83.48 m of Bengawan Solo water level, for reducing water level of Boro river flooding. Keywords: Flood, drainage systems, floodgate and flow routing.